2016
DOI: 10.1038/srep34223
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic MKP-1 is a Sensor of the Metabolic Environment and Regulates Function and Phenotypic Fate of Monocyte-Derived Macrophages in Atherosclerosis

Abstract: Diabetes promotes the S-glutathionylation, inactivation and subsequent degradation of mitogen-activated protein kinase phosphatase 1 (MKP-1) in blood monocytes, and hematopoietic MKP-1-deficiency in atherosclerosis-prone mice accelerates atherosclerotic lesion formation, but the underlying mechanisms were not known. Our aim was to determine the mechanisms through which MKP-1 deficiency in monocytes and macrophages promotes atherogenesis. Transplantation of MKP-1-deficient bone marrow into LDL-R−/− (MKP-1LeuKO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 61 publications
2
25
1
Order By: Relevance
“…More recently, it was reported that histone H3 also interacts with and is dephosphorylated by MKP-1 to mediate epigenetic regulation on vascular endothelial growth factor (VEGF)-induced gene transcription [66]. In agreement with this report, we found that histone H3 phosphorylation (Ser10) was increased in the MKP-1-deficient macrophage exposed to metabolic stress [21], making H3 the only known bona fide non-MAPK substrate candidate for MKP-1.…”
Section: Mkp-1 – Structure Functions and Regulationsupporting
confidence: 88%
See 3 more Smart Citations
“…More recently, it was reported that histone H3 also interacts with and is dephosphorylated by MKP-1 to mediate epigenetic regulation on vascular endothelial growth factor (VEGF)-induced gene transcription [66]. In agreement with this report, we found that histone H3 phosphorylation (Ser10) was increased in the MKP-1-deficient macrophage exposed to metabolic stress [21], making H3 the only known bona fide non-MAPK substrate candidate for MKP-1.…”
Section: Mkp-1 – Structure Functions and Regulationsupporting
confidence: 88%
“…Compared with wild-type mice, MKP-1–deficient mice produced substantially greater amounts of TNF, IL-1β, CC-chemokine ligand 2 (CCL2; also known as MCP1), granulocyte/macrophage colony-stimulating factor (GM-CSF), IL-6, IL-10 and IL-12p70 and showed a considerably higher incidence of multi-organ failure and mortality after LPS challenge in vivo compared with wild-type mice [25, 121, 122]. These findings are consistent with our report mentioned above that MKP-1 deficiency induced by metabolic stress predisposing macrophages to a hyper-inflammatory M1-like polarization state [21]. …”
Section: Mkp-1 – Role In Monocytes and Macrophagessupporting
confidence: 85%
See 2 more Smart Citations
“…In some cases, exposure of macrophages to increased nutrients increase their inflammatory activation 911 . Thus, the nutritional state of the cell governs activation of the LKB1/AMPK pathway (in states of nutrient deprivation) and inflammatory activation in response to LPS and other inflammatory mediators (in states of nutrient plenty).…”
mentioning
confidence: 99%